Do elite event riders use scientific training principles to prepare their horse for competition? - Lewis, V.; Dixon, S. (DCA Report; Nr. 044, 2014)
Empirical sports research suggests most athletes utilize a training programme incorporating scientific sports theories such as the principles of training and periodization to enhance and organize the training undertaken to prepare for competition. However, the training programmes used by elite event riders for their horses have not been researched although there is lay evidence that they are incorporated. The aim of this study was to fill the gap in the research and to investigate whether scientific sports principles are used by elite event riders to prepare their horses for competition. The objectives were to compare and contrast the training programmes used by 5 elite event riders utilizing qualitative research methods to identify how scientific training principles have been used to devise training. The participants consisted of 5 elite event riders who have completed CCI**** level events. Semi-structured interviews were the selected study method for data collection to solicit the experiences and opinions of the participants in regard to elite event horse training programmes. The interviews were analysed using content analysis and the results were presented using a thematic structure form. Thematic analysis of the data revealed there were 663 meaningful units represented as first order themes. The three main categories the themes fell into were `Meet physiological demands of eventing` `Training Programme Design` and `Periodization`. The study`s findings revealed that elite event riders undertake training incorporating scientific training principles such as the principles of training to enhance the horse`s performance, reduce the risk of injury and to meet the physiological demands of eventing. However, each rider`s training programme was different suggesting there is not a strict, set programme for elite event riders to use. The highest recurring themes revealed by the data and the primary deciding factors for training allocation was specificity to the individual horse and ensuring that training was specific to the demands of eventing therefore ensuring maximum preparation for competition. Training was also highly influenced by the facilities available to the rider as both gradient and a variety of surfaces were used to mimic what is found at competitions and to increase training efficiency. Periodization of an elite event horse`s training programme is utilized to add structure and organisation of the phases of the year. The data suggests a two peak periodization model is often used by elite event riders to accommodate there being two major competitions in the season for an elite event horse. LP: In sport, athletes utilize tailored and structured training programmes to prepare themselves for the demands of competition. This study suggests that elite event riders use scientific training principles to prepare their horses for competition. Therefore, knowledge and understanding of scientific training principles is needed to successfully structure a training programme for eventing.